2021
DOI: 10.3389/fmicb.2021.755155
|View full text |Cite
|
Sign up to set email alerts
|

Transovarial Transmission of Dolichos Yellow Mosaic Virus by Its Vector, Bemisia tabaci Asia II 1

Abstract: The cultivation of dolichos bean [Lablab purpureus (L.) Sweet] has been severely affected by dolichos yellow mosaic virus (DoYMV, Begomovirus) transmitted by whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae). We tested the transovarial transmission of DoYMV in next-generation B. tabaci by PCR, real-time PCR, Southern blot hybridization, and biological transmission. The eggs, laid by DoYMV-exposed B. tabaci, carry the virus in a unique pattern. Only the eggs laid in between 3 and 6 days post virus acquisition b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This is how the whitefly transmission of begomovirus is referred as a circulative persistent mode of transmission. However, while persisting in the whitefly body, viral replication and transovarial transmissions of begomovirus is not clear yet, as the current studies have shown inconsistent results (Ghanim et al, 1998;Bosco et al, 2004;Becker et al, 2015;Sanchez-Campos et al, 2016;Fiallo-Olive and Navas-Castillo, 2019;Guo et al, 2018;Ghosh et al, 2021).…”
Section: Begomovirus Transmission Processmentioning
confidence: 69%
“…This is how the whitefly transmission of begomovirus is referred as a circulative persistent mode of transmission. However, while persisting in the whitefly body, viral replication and transovarial transmissions of begomovirus is not clear yet, as the current studies have shown inconsistent results (Ghanim et al, 1998;Bosco et al, 2004;Becker et al, 2015;Sanchez-Campos et al, 2016;Fiallo-Olive and Navas-Castillo, 2019;Guo et al, 2018;Ghosh et al, 2021).…”
Section: Begomovirus Transmission Processmentioning
confidence: 69%
“…RFA1 is an ssDNA binding protein ( Wold, 1997 ). Although replication factors play an important role in DNA replication, recombination, and repair ( Vanoli et al, 2010 ; Yamamoto et al, 2019 ), ChiLCV-DNA does not replicate within the vector ( Rosen et al, 2015 ; Ghosh et al, 2021 ). This rejected the possibility of involvement of RFA1 in virus multiplication in B. tabaci .…”
Section: Discussionmentioning
confidence: 99%
“…TYLCV, tomato yellow leaf curl China virus (TYLCCNV), tomato leaf curl Bangalore virus (ToLCBaV), papaya leaf curl China virus (PaLCuCNV), tomato leaf curl Taiwan virus (ToLCTWV), tomato yellow leaf curl Thailand virus (TYLCTHV), euphorbia yellow mosaic virus (EuMV), and tobacco curly shoot virus (TbCSV) are transmitted by different B . tabaci cryptic species at varying efficiencies [ 34 , 40 42 , 47 55 ]. A steady increase in the ToLCNDV copies was observed 6 hrs post feeding.…”
Section: Discussionmentioning
confidence: 99%